2021
DOI: 10.1111/jog.15061
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pregnancy and live birth rates after in vitro fertilization in women with cesarean section scar diverticulum: A retrospective cohort study

Abstract: Aim: The primary aim of the study was to investigate the effect of cesarean scar diverticulum on the reproductive outcome of embryo transfer. The secondary aim was to assess the impact of endometrial cavity fluid on the reproductive outcome of embryo transfer among patients with a cesarean scar diverticulum. Methods: This was a retrospective cohort study. The study included 1538 patients, of whom 215 patients with an existing cesarean scar diverticulum and 1323 patients without cesarean scar diverticulum. A su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Patients with CSD were associated with a significantly lower rate of subsequent live birth (aOR: 0.609, 95%CI: 0.476~0.778, P <0.001) and clinical pregnancy (aOR: 0.779, 95%CI: 0.623~0.973, P =0.027), as well as a higher likelihood of miscarriage (aOR:1.407, 95%CI: 1.03~1.923, P =0.032) compared with those without defect at the site of the cesarean incision. The results were in agreement with previous studies ( 21 , 35 ). The existence of CSD could lead to poor pregnancy outcomes in patients undergoing IVF.…”
Section: Discussionsupporting
confidence: 94%
“…Patients with CSD were associated with a significantly lower rate of subsequent live birth (aOR: 0.609, 95%CI: 0.476~0.778, P <0.001) and clinical pregnancy (aOR: 0.779, 95%CI: 0.623~0.973, P =0.027), as well as a higher likelihood of miscarriage (aOR:1.407, 95%CI: 1.03~1.923, P =0.032) compared with those without defect at the site of the cesarean incision. The results were in agreement with previous studies ( 21 , 35 ). The existence of CSD could lead to poor pregnancy outcomes in patients undergoing IVF.…”
Section: Discussionsupporting
confidence: 94%
“…Although natural birth is still the most common form of delivery, increasingly more pregnant women are choosing painless birthing options, such as water delivery and cesarean section ( Fobelets et al, 2019 ), especially those with a narrow pelvis, abnormal placenta, abnormal birth canal, premature water rupture, and abnormal fetus. However, post-cesarean section scar diverticulum (PCSD), which generally refers to lacunae formed as a result of poor healing of the uterine incision after the cesarean procedure ( Zheng et al, 2020 ; Huang et al, 2022 ), is a common condition that can cause many problems in the new mother, such as chronic inflammation ( Negro et al, 2017 ; Bi et al, 2021 ). Therefore, new medical strategies are required to effectively reduce the occurrence of PCSD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that women with isthmocele may experience reduced pregnancy and live birth rates following IVF procedures [127]. Additionally, isthmocele can lead to challenges during embryo transfer due to distorted anatomy, particularly in cases of a retroflexed uterus [128].…”
Section: Discussionmentioning
confidence: 99%